Building Bonds And Breaking News: Exploring Male Journalists’ Personal Relationship Challenges - Balagan, Sheila May; Eslava, Maria Karmeena; Montojo, Christine Nicole; Ordinario, Marie Carisa (Informasi, 2025)
Workplace conditions significantly impact journalists' work-life balance and psychological well-being. This study explores male journalists' challenges in maintaining personal relationships outside of work via a phenomenological approach using purposive and non-proportional sampling to understand how they experience newsroom demands and balance their relationships. Respondents revealed the complexities of balancing such relationships and their professional responsibilities. The study identified three main themes: the impact of newsroom demands on work-life balance and romantic prospects, coping mechanisms and boundary management, and conflict resolution outside work. Researchers also saw a divide between older and younger participants regarding these themes. These findings provided valuable insights into the challenges faced by male Filpino journalists and the strategies they employ to navigate their personal and professional lives. Recommendations emphasize the need for tailored support systems within newsrooms. By advocating for policy changes such as respecting journalists' time off, newsrooms can foster an environment that protects their well-being.